The Role of Artificial Intelligence in Modern Accounting: A Systematic Literature Review - Nayla Safarah; Gunawan Aji (Yayasan Abdurrauf Cendekia Nusantara, 2025)
The development of artificial intelligence (AI) technology has brought significant changes to accounting and auditing practices, particularly in automating processes and supporting data-driven decision-making. This study aims to analyze the role of AI in improving the effectiveness and efficiency of the auditing process and to identify the ethical implications arising from its use. The method used is a Systematic Literature Review (SLR) with a qualitative approach, using the PRISMA protocol to screen 24 journal articles from 2015 to 2024. The results of the study show that AI can improve accuracy, efficiency, and support real-time risk-based auditing. However, ethical challenges such as lack of transparency, algorithmic bias, and threats to professional independence remain important issues. Therefore, the successful application of AI in auditing is not only determined by technological sophistication, but also by the ethical readiness and digital literacy of auditors. This study confirms that the integration of AI in modern auditing has great transformative potential if balanced with responsible governance and oversight.